Synthesis, biological evaluation and molecular docking investigation of new sulphonamide derivatives bearing naphthalene moiety as potent tubulin polymerisation inhibitors - Guangcheng Wang; Meiyan Fan; Wenjing Liu; Min He; Yongjun Li; Zhiyun Peng (Taylor & Francis Group, 2021)
A new series of sulphonamide derivatives bearing naphthalene moiety were synthesised and evaluated for their antiproliferative and tubulin polymerisation inhibitory activities. These new compounds were evaluated for their in vitro antiproliferative activity against MCF-7 and A549 by using CCK-8 method. Among all the tested compounds, compound 5c with naphthalen-1-yl moiety exhibited the most potent antiproliferative activity against MCF-7 and A549 cell line, with IC50 values of 0.51 ± 0.03 µM and 0.33 ± 0.01 µM, respectively. The results of tubulin polymerisation assay shown that 5c exhibited a significant ability to inhibit tubulin polymerisation with IC50 value of 2.8 μM. Consistent with its antitubulin activity, 5c can significantly arrest the cell cycle at G2/M phase and induce apoptosis in MCF-7 cancer cells. Molecular docking study indicated that compound 5c inhibited tubulin polymerisation through interacting at the colchicine-binding site of tubulin. Furthermore, 5c exhibited low cytotoxic activity on human normal cell line.